A simultaneous determination of rifampin and 25-desacetylrifampin in cerebrospinal fluid and plasma of rabbit by liquid chromatography - Chan Kelvin (Acta Pharmacologica Sinica; Vol 8, No 6 (November 1987): Acta Pharmacologica Sinica, 2016)
A liquid chromatographic assay was modified for the simultaneous determination of rifampin (R) and its major metabolite, 25-desacetylrifampin (25-DR) in cerebrospinal fluid (CSF) and plasma in the rabbit. R, 25-DR and the internal standard, p-methylaminobenzoic acid (PMAB), were in an acidified sample at pH 4.2 containing 2% ascorbic acid as anti-oxidant and extracted into organic solvent (diethylether:dichloromethane, 3:2). The residue of the solvent extract was dissolved in 75μl methanol. The concentration was analysed by a liquid chromatograph consisting of a LDC pump using a reversed phase pre-column (30μm C8) linked to a radial pak column (10μm C8). The compounds were eluted with acetonitrile-l0 mmol/L phosphate buffer, KH2PO4, at pH 3.5 (40:60, vol:vol). The eluates are detected at 254 nm. The assay has been used to investigate the disposition of R and 25-DR in CSF and plasma of the rabbits.